2018
DOI: 10.1021/acsaem.8b01389
|View full text |Cite
|
Sign up to set email alerts
|

Nonstoichiometric Triazolium Protic Ionic Liquids for All-Organic Batteries

Abstract: Nonstoichiometric protic ionic liquids (NSPILs) are efficient electrolytes for protic electrochemical devices such as the allorganic proton battery, which has been suggested as a sustainable approach to energy storage. NSPILs contain a mixture of proton donors and acceptors and are ideal for this purpose due to their high proton conductivity, high electrochemical stability, low cost, and ease of synthesis. However, the electrolyte proton activity must be controlled carefully in these devices since it greatly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 34 publications
2
56
0
Order By: Relevance
“…Different from the common approach of employing ILs as a “solvent” for the conducting salt, Karlsson et al. reported the use of nonstoichiometric protic ILs as electrolytes for completely metal‐free all‐organic proton batteries . In this case, molecules such as 1,2,4‐triazole or 1‐methyl‐1,2,4‐triazole act as a proton acceptor and their protonated derivatives, which are counterbalanced by the TFSI − anion, serve as a proton donor.…”
Section: Electrolytes For Redox Organic Electrodesmentioning
confidence: 99%
“…Different from the common approach of employing ILs as a “solvent” for the conducting salt, Karlsson et al. reported the use of nonstoichiometric protic ILs as electrolytes for completely metal‐free all‐organic proton batteries . In this case, molecules such as 1,2,4‐triazole or 1‐methyl‐1,2,4‐triazole act as a proton acceptor and their protonated derivatives, which are counterbalanced by the TFSI − anion, serve as a proton donor.…”
Section: Electrolytes For Redox Organic Electrodesmentioning
confidence: 99%
“…The acidity and relative fraction of the protonated (acid) and the unprotonated (base) heterocycle moieties can be used to tune both the kinetics and the energetics of proton-coupled redox reactions. 37 …”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23] By replacing the water solvent it should therefore be possible to increase the stability of proton batteries by suppressing the Michael addition reaction. This could be done in organic protic electrolytes [24] or using nonstoichiometric protic ionic liquids, [25] which also could allow a potential window over 1.23 V. [26][27][28] We have previously shown that the use of non-aqueous solvents significantly extends the possibility to tune quinone redox potentials by substitution, since in aqueous solution, specific interactions with water molecules counteract the effect of the substituents. [29] Finally, protic ionic liquids may provide a solution for redox-active materials that show poor wettability in water electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…The acidity and relative fraction of the protonated (acid) and the unprotonated (base) heterocycle moieties can be used to tune both the kinetics and the energetics of proton coupled redox reactions. [25] Herein, a 1-methyl-1,2,4-triazole (MeTri) based ionic liquid (pKa = 3.2) was used as electrolyte together with conducting redox polymer (CRP) electrode materials. Capacity-carrying quinizarin (1,4-dihydroxyanthraquinone, Qz) and NQ pendants covalently attached onto a conducting polymer backbone were used as cathode and anode, respectively.…”
Section: Introductionmentioning
confidence: 99%